Application of the Science Technology Society (STS) Model to Craft and Entrepreneurship Materials to Develop Soft Skills of Students - Fira Roswita; Sulastri Sulastri; Ibnu Khaldun (Postgraduate, University of Mataram, 2021)
The development of information technology requires students to have life skills when they enter workplaces. Soft skills are one of the skills that students must have. This research aims to analyze the application of the science technology society (STS) model to develop their soft skills. The method used in this research is a pre-experimental design with a one-shot case study design. The population was the students of class XI MIA with simple random sampling used as the sampling technique, and the research subjects were thirty-two (32) students of class XI MIA 2 that were divided into six groups. The results showed that the application of STS-based student worksheets could develop their soft skills about 88.15%, categorized as very good, and had high qualifications